2010
DOI: 10.1007/s10549-010-0757-7
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor-induced arthralgia in early breast cancer: what do we know and how can we find out more?

Abstract: Aromatase inhibitors (AIs) are a standard of care for the adjuvant treatment of hormone responsive early carcinoma of the breast as demonstrated in a number of large international phase III randomised trials. Arthralgia was a somewhat unexpected side effect of this class of agents and has proven to be potentially problematic in clinical practice. Although rates of up 35% have been reported in the randomised trials, the figure has been much higher in subsequent case series. There is concern that these symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 89 publications
0
59
0
Order By: Relevance
“…However, through their ability to profoundly suppress circulating and tissue based estrogens, AI are associated with musculoskeletal adverse events. These include arthralgia and accelerated bone loss which may lead to fragility fractures [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, through their ability to profoundly suppress circulating and tissue based estrogens, AI are associated with musculoskeletal adverse events. These include arthralgia and accelerated bone loss which may lead to fragility fractures [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies of women receiving ais as adjuvant treatment have reported rates of 47% 8 and as high as 61% 16 . Regardless of the incidence, it is clear that ai treatment is associated with a degree of arthralgia requiring medical attention, and this aspect of ai treatment is being evaluated in a number of ongoing studies 3 . In our study, awareness that all women had msk conditions at baseline and regular monitoring of pain symptoms made it possible to keep the symptoms under control.…”
Section: Discussionmentioning
confidence: 99%
“…Slightly higher levels of 1,25(OH) 2 vitamin D 3 were observed at baseline in patients with pain increase, but did not significantly change during treatment; however, average levels of 25(OH) vitamin D 3 increased, likely because of supplementation. Although biochemical markers did not discriminate efficiently between pain groups, a signature of 166 genes in peripheral blood mononuclear cells was identified that could stratify patients into the various groups observed in this pilot study.…”
mentioning
confidence: 84%
See 2 more Smart Citations